AB0037 NEUTROPHIL GRANULOCYTES ARE PRIMED IN CHILDREN WITH JUVENILE IDIOPATHIC ARTHRITIS (JIA). (June 2019) - Berntson, Lillemor; Kihlberg, Ulrika; Venge, Per
Abstract : Background: The adaptive as well as innate immunity is involved in JIA pathology. Neutrophils are key mediators of the innate immune response and is the most abundant cell type found in JIA synovial fluid. Studies of neutrophils in JIA have shown transcriptional abnormalities and neutrophil-derived S100A proteins have shown a potential role as biomarkers. Still, studies of neutrophils in JIA are scarce. Human neutrophil lipocalin (HNL), also known as neutrophil gelatinase-associated lipocalin (NGAL), is a protein found in the secondary granules of neutrophil granulocytes. HNL can be found in epithelial cells as well, but only in its monomeric form. The dimeric form is only produced by neutrophil granulocytes. HNL resides in the secondary granules and is released upon stimulation, making HNL a unique marker of primed and activated neutrophil granulocytes, compared to myeloperoxidase (MPO) that resides in the primary granules and is released when neutrophils are activated, but also found in monocytes. Objectives: To examine levels of the dimeric form of human neutrophil lipocalin (dHNL), to reveal if neutrophil granulocytes are primed in JIA, also analysis of myeloperoxidase MPO to reveal neutrophil activation. We aimed to compare the analyses to healthy controls and correlate the results to established measures of disease activity. Methods: Blood samples from 75 patients with JIA (68% females) and 16 healthy controls were analyzed regarding HNL, using a dimer ELISA assay (Diagnostics Development, Uppsala, Sweden) specifically detecting the dimeric form of HNL (dHNL). We also analysed MPO (Diagnostics Development, Uppsala, Sweden), white blood cell count, neutrophil granulocyte cell count, ESR and CRP. All categories of JIA except the systemic category were included. Patient/parent and the physician filled out a global health assessment on a VA-scale (0-10). The number of active joints at sampling was collected and patients were classified according to the ILAR criteria. The participants with JIA had a median age of 12.1 (IQR: 7.7-15.3) years, the control group 5.3 (IQR: 2.0-9.5) years. Results: The serum levels of dHNL and MPO were significantly elevated compared to healthy controls, (p < 0.001; p =0.002), and correlated significantly with each other (rs =0.68, p <0.001). The levels of dHNL correlated best to the count of neutrophil granulocytes (rs =0.54, p <0.001), total leukocyte count (rs =0.43, p<0.001) and less well to CRP (rs =0.42, p <0.001) and ESR (rs =0.35, p =0.002) and not at all to the scoring system for disease activity, JADAS27 (rs =0.06, p =0.65). Conclusion: The increased levels of the dimeric HNL in serum confirmed the involvement of neutrophil granulocytes in JIA although dHNL did not correlate with disease activity. The mechanisms by which neutrophils are primed and activated in JIA, however, still remain an enigma. Disclosure of Interests: Lillemor Berntson Consultant for: AbbVie, Speakers bureau: AbbVie, Ulrika Kihlberg: None declared, Per Venge: None declared